Response time with successful handling on call patient stroke - Aandarini, Deci; Susaldi, Susaldi; Suryadi, Bambang (University of Muhammadiyah Malang, 2024)
Introduction: Stroke is a dangerous disease and can cause disability and death. Stroke is the second cause of death and the third cause of disability in the world. Stroke requires quick treatment to minimize disability and death. The impact that results if stroke treatment is delayed is that it can result in permanent disability and death. Objectives: The aim of this research is to determine the relationship between response time and successful treatment of oncall stroke patients at PSC 119 Depok in 2023. Methods: The research method that will be used is an analytical research design with a correlational cross-sectional approach, population of 80 respondents, total sample technique and sample size of 30 respondents. Using the Chi-Square parametric test. Results: The results describe the characteristics of respondents, age 20 years – 40 years (83.3%), D3 education in nursing (83.3%), gender female (63.3%), length of work ≥ 5 years (90%). The description of the response time is less fast (63.3%). description of successful treatment of oncall stroke patients who were unsuccessful (66.7%) There is a relationship between response time and successful treatment of oncall stroke patients at PSC 119 Depok in 2023, p-value 0.023 < 0.05 and OR = 9.333. Conclusions: Conclusion response time influences the success of stroke treatment.